Enhanced solar energy absorption in PCM-integrated corrugated wick distillers using ZnO nanoparticles and activated carbon - Palaniappan, Murugesan; Alrasheedi, Nashmi H.; Kavitha, A.; Sangeetha, T.; Keerthika, N.; Usha, R. Josephine; Selvaraju, P.; Shanmugan, S. (Frontiers in Water, 2025)
This study examines a single-slope corrugated wick solar distillation system enhanced with a hybrid nanocomposite made of zinc oxide (ZnO) nanoparticles and activated carbon (AC) to improve solar radiation capture and maximize photothermal energy conversion. By mediating non-radiative energy exchange between the photonic field and water molecules, Forster Resonance Energy Transfer (FRET) plays a crucial role in enhancing localized thermal interactions at the saline interface. The integration of these nanomaterials promotes better thermal energy coupling. To capture and hold onto solar thermal energy as latent heat during periods of high irradiation, the system also includes a paraffin-based phase change material (PCM), which is positioned strategically beneath the wick absorber. Even in the absence of direct solar input, this stored energy is progressively released over the post-sunset hours, allowing for continued temperature regulation and prolonged nighttime distillate production. Experiments conducted under normal atmospheric and sunlight conditions demonstrate significant improvements over traditional wick-type distillers. With a matching thermal efficiency of 42.53% and an average distillate yield of 5.123 L·m−2·day−1, the new configuration outperformed the control system by 42%. Significantly, on days with constant solar irradiation, the mean evaporative heat transfer coefficient was found to be around 157 W·m−2, demonstrating an effective energy flux between the water layer and wick surface. A combined impact of improved light absorption, greater surface thermal conductivity, and efficient non-contact energy propagation made possible by the FRET mechanism is responsible for the observed improvement in distillation performance. The PCM’s controlled exothermic discharge greatly promotes continuous distillate output during off-peak hours, which helps to maintain the system’s operational continuity and energy autonomy. In addition to redefining the thermal management approach in passive solar desalination systems, the combination of FRET-driven energy dynamics and phase change storage paves the way for next-generation hybrid designs targeted at water-scarce regions with fluctuating sun availability.